THE EFFECTIVENESS OF STUDENTS’ VOCABULARY IN READING COMPREHENSION USING DIRECT METHOD TECHNIQUE TO THE SECOND SEMESTER STUDENTS AT UNIVERSITY OF PGRI - Dewi Kartika Sari (Universitas PGRI Palembang, 2018)
Abstract: Language is a mean of communication. To understand the language, we have to invent the meaning of words as many as possible either in a sentence or in whole texts. Vocabulary is one of the most important elements in a language, and teaching vocabulary is clearly more than presenting new words. Reading comprehension depends on several interrelated skills: understanding oral language, decoding the printed words, reading fluently, and using strategies to increase comprehension. Understanding reading material needs a specific reading strategy. The strategy should facilitate the comprehension of the students who want to read effectively. One of the techniques which can be used is Direct Method. The idea of this technique was that foreign language teaching must be carried out in the same way people learn their mother tongue